La investigación en Teoría de la Educación - Martínez Martín, Miguel; Buxarrais Estrada, M. Rosa (Teoría de la Educación. Revista Interuniversitaria, 2009)
This paper establishes as types of knowledge in the Theory of education the scientific and ordinary knowledge. We consider discursive and reflexive dimensions in this area with other dimensions looking for a relationship between the theory and the practice in a circular pattern of doing knowledge in order to obtain the optimization of the efficacy in the pedagogical action. It frames different prior areas of study and research considering an analysis of the research in the Theory of education carried out in the period of 1989-1991 in Spain. We defend a kind of methodology that overcomes the limits of classic paradigms, it was found that it has a minimal intervention of the researcher, high levels of molarity, and preserving the maximum level of rigour and validity.